Experimental evaluation of FSM-based testing methods; Software Engineering and Formal Methods: SEFM 2005 - Dorofeeva M. Yu. Margarita Yurievna; El-Fakih Kh.; Maag S.; Cavalli A. R.; Yevtushenko N. (2005, 2005)
Title screen